1961
DOI: 10.2170/jjphysiol.11.44
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of the Cardioregulatory and Abdominal Sympathetic Nerves During Swallowing

Abstract: It has been stated that the swallowing acts are accompanied with changes of the respiratory9,14-16,18,19,22) and gastrointestinal movements4,7.23) as well as changes of the cardiovascular system. Concerning the changes of the circulatory system during deglutition some authors7,16,22,23) have reported various

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1995
1995

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In fact, it starts before the appearance of esophageal peristalsis and does not take place after balloon stimulation. Animal experi ments demonstrated that this increase in heart rate is achieved through an inhibition of tonic vagal activity to the heart induced by deglutition [18]. The alteration of this central effect of deglutition may lead to supraventric ular tachyarrhythmias [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it starts before the appearance of esophageal peristalsis and does not take place after balloon stimulation. Animal experi ments demonstrated that this increase in heart rate is achieved through an inhibition of tonic vagal activity to the heart induced by deglutition [18]. The alteration of this central effect of deglutition may lead to supraventric ular tachyarrhythmias [19][20][21].…”
Section: Discussionmentioning
confidence: 99%